Long‐Term Measures of Dyslipidemia, Inflammation, and Oxidative Stress in Rats Fed a High‐Fat/High‐Fructose Diet. Issue 1 (14th February 2019) - Feillet‐Coudray, Christine; Fouret, Gilles; Vigor, Claire; Bonafos, Béatrice; Jover, Bernard; Blachnio‐Zabielska, Agnieszka; Rieusset, Jennifer; Casas, François; Gaillet, Sylvie; Landrier, Jean Francois; Durand, Thierry; Coudray, Charles
Abstract: Inflammation and oxidative stress are thought to be involved in, or associated with, the development of obesity, dyslipidemia, hepatic steatosis, and insulin resistance. This work was designed to determine the evolution of inflammation and oxidative stress during onset and progression of hepatic steatosis and glucose intolerance. Seventy‐five male Wistar rats were divided to control and high‐fat high‐fructose (HFHFr) groups. A subgroup of each group was sacrificed at 4, 8, 12, 16, and 20 weeks. HFHFr‐fed rats exhibited overweight, glucose intolerance, and hepatic steatosis with increased contents of hepatic diacylglycerols and ceramides. The HFHFr diet increased hepatic interleukin 6 (IL‐6) protein and adipose tissue CCL5 gene expression and hepatic nicotinamide adenine dinucleotide phosphate (NADPH) oxidase activity but not mitochondrial reactive oxygen species (ROS) production. The HFHFr diet decreased plasma and liver levels of isoprostanoid metabolites as well as plasma thiobarbituric acid‐reactive substance (TBARS) levels. Hepatic glutathione content was decreased with a moderate decrease in superoxide dismutase (SOD) and glutathione peroxidase (GPx) with the HFHFr diet. Overall, HFHFr diet led to hepatic lipid accumulation and glucose intolerance, which were accompanied by only moderate inflammation and oxidative stress. Most of these changes occurred at the same time and as early as 8 or 12 weeks of diet treatment. This implies that oxidative stress may be the result, not the cause, of these metabolic alterations, and suggests that marked hepatic oxidative stress should probably occur at the end of the steatotic stage to result in frank insulin resistance and steatohepatitis. These findings need to be further evaluated in other animal species as well as in human studies.